Hubungan keseimbangan dengan kemampuan shooting atlet futsal kawat duri u-14 - Yoga Teja Kartika; Prisca Widiawati (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2025)
This study aims to identify the relationship between balance and shooting ability in U-14 futsal athletes of Kawat Duri. The research uses a descriptive quantitative approach and is a non-experimental study with a survey method. The population consists of all male U-14 athletes at the Kawat Duri futsal club, totaling 21 individuals, and total sampling was applied. Data collection was done using tests and measurements. Data analysis used correlation techniques, which showed a positive correlation between balance and shooting ability with a correlation value of 0.778. The coefficient of determination (R²) indicates that balance contributes 61% to shooting ability. The conclusion of this study is that the better the athlete's balance, the higher their shooting ability, emphasizing the importance of balance in improving shooting performance in futsal..